Perspective: host factors variants and the underlying causes of long COVID - Pasharawipas, Tirasak (Frontiers in Medicine, 2025)
Long COVID, also known as post-COVID syndrome (PCS), is characterized by persistent and unexplained symptoms that can occur not only in individuals who experienced severe symptoms during the acute phase of SARS-CoV-2 infection but also in those who were asymptomatic or had only mild symptoms. These symptoms may persist for months, even in individuals who test negative via nasopharyngeal swab samples. This proposal aims to explain the cause of long COVID through the concept of host factor variants, including cellular variants and major histocompatibility complex (MHC) polymorphisms. A key aspect of this hypothesis is the role of antigen-presenting cells, such as macrophages and dendritic cells. It is proposed that blood or white blood cells could serve as suitable samples for diagnosing long COVID in affected individuals.